Poor Lymphocyte Infiltration to Primary Tumors in Acral Lentiginous Melanoma and Mucosal Melanoma Compared to Cutaneous Melanoma - Nakamura, Yoshiyuki; Zhenjie, Zhu; Oya, Kazumasa; Tanaka, Ryota; Ishitsuka, Yosuke; Okiyama, Naoko; Watanabe, Rei; Fujisawa, Yasuhiro (Frontiers in Oncology, 2020)
Recent clinical trials have demonstrated the efficacy of immune checkpoint inhibitors (ICIs) for treating melanoma. However, these previous studies comprised mainly Caucasian populations, in which cutaneous melanoma (CM) is the major clinical type. In contrast, Asian populations have a distinct profile of melanoma and show much higher frequencies of acral lentiginous melanoma (ALM) and mucosal melanoma (MCM). Compared with CM, ALM and MCM show poorer response to ICIs, but the mechanisms have not been fully understood. To evaluate the immune status in each melanoma subtype, we examined the number of total tumor-infiltrating lymphocytes (TILs), CD4+ TILs, CD8+ TILs, and tumor-infiltrating FoxP3+ regulatory T cells (Tregs) to evaluate the immune status in each melanoma subtype using data from 137 patients with melanoma. Total TIL numbers in ALM and MCM were significantly lower than that in CM. CD4+ TIL number in MCM was also lower than CM although CD4+ TIL number in ALM was comparable with CM. In contrast, CD8+ TIL numbers in both ALM and MCM were significantly lower than that in CM. Although number of tumor-infiltrating Tregs was comparable among the 3 subtypes, the proportion of tumor-infiltrating Tregs in CD4+ T cells in MCM was significantly higher than in CM and ALM. Multivariate regression analysis revealed that ALM and MCM were significantly associated with a lower total TIL number, but only MCM was significantly associated with a lower CD4+ TIL number. Multivariate regression analysis also revealed that both ALM and MCM were significantly associated with a lower CD8+ TIL number. Our results suggest that both ALM and MCM are independent factors of lower total TIL number, which may be associated with poorer responses to ICIs in ALM and MCM.